PEMBAKARAN SAMPAH ANORGANIK MENIMBULKAN DAMPAK POSITIF DENGAN PEROLEHAN ASAP CAIR BAGI MASYARAKAT LINGKUNGAN IX KECAMATAN AMPLAS - Suhardi Napid; Rahmad Setia Budi; Edi Susanto (Jurnal Pengabdian Mitra Masyarakat, 2021)
The impact of open burning of garbage can actually be detrimental to the surrounding community, both for health and the environment. The problem faced by the community of Environment IX in Siti Rejo III Village is the increasing number of piles of garbage with an unpleasant aroma in the riverbank flow area, this means that community awareness is still low so that it littering. The aim of the community service is to obtain liquid smoke from closed burning of garbage on the edge of the river area. The method of implementing the activity is counseling / directing to local residents. A number of inorganic waste is put into the incinerator and then immediately closed tightly with a cover for burning the garbage when the blower is on. The solution to this problem is to build a closed furnace for burning waste. The results of the burning of inorganic waste carried out by local residents in various places (land) along the river can produce liquid smoke which is useful for pesticides, food preservatives, etc. It can directly reduce environmental pollution because emissions from burning waste will be reduced with the consequence of reducing the volume of waste. As a result of this activity, the community has been able to carry out a technique of burning garbage with a closed system where the smoke spreads to the pipe installation with the output producing liquid smoke that does not cause environmental pollution. Therefore, it is deemed necessary immediately to build several units of closed stoves for burning garbage around the river